Traditional Games as a Media for Embed the Pancasila Profile of Early Childhood Students (Current Research in Education: Conference Series Journal, 2024)
This article aims to determine the role of traditional games to embed an independent dimension of the Pancasila student profile in early childhood. The writing method in this article is a systematic review. The sources of main data in this research are scientific articles that are relevant to the topic of study. Based on the results of identification, evaluation and interpretation, it can be concluded that traditional games act as a learning media for early childhood. Traditional games are used as a media to stimulate children's character learning, including the independent dimension in the Pancasila student profile. There are some traditional games can develop an independent dimension in early childhood, such as: gobak sodor, engrang, engklek and petak umpet. The dimension of independence in traditional games reflected when the children can be positioning themselves in a game as part of a group, and they can to express the emotions naturally.